The Influence of Low HLA-G Protein Expression on Hsp-70 and VCAM-1 Profile in Preeclampsia - Sri Sulistyowati (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To analyze HLA-G, Hsp-70, and VCAM-1 proteins expression on trophoblast in women with preeclampsia and women with normal pregnancy, and to assess causality relationship between low HLA-G expression and the increased Hsp-70 and VCAM-1 expression in preeclampsia. Method: Observational analytic study with cross sectional design. Results: Trophoblastic HLA-G expression in pregnant women with preeclampsia is lower (p = 0.01) than its expression in women with normal pregnancy. The expressions of Hsp-70 (p = 0.02) and VCAM-1 (p = 0.00) in preeclampsia are higher, compared to normal pregnancy. Regression analysis showed that low HLA-G is a predictor for the increase of trophoblastic Hsp-70 and VCAM-1. Conclusion: Low trophoblastic HLA-G in is a predictor for endothelial dysfunction in women with preeclampsia. [Indones J Obstet Gynecol 2010; 34-4: 185-90] Keywords: preeclampsia, HLA-G, Hsp-70, VCAM-1, endothelial dysfunction